The Influence of Leadership Style on Employee Performance through Organizational Culture at PT PLN (Persero) ULP Mattoanging - Regina Dian Pratiwi; Jayadi (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2025)
The importance of effective human resource management has increased significantly in the face of globalization and growing competition, as employees play a central role in achieving organizational strategic goals. This study aims to find out the leadership style, organizational culture, and employee performance, as well as the influence of leadership style on employee performance, the influence of leadership style on organizational culture, the influence of organizational culture on employee performance, and the indirect influence of leadership style on employee performance through organizational culture. The study population included 97 employees of PT PLN (Persero) ULP Mattoanging, with a sample of 50 permanent and contract employees selected through purposive sampling techniques. This study used a quantitative method with a descriptive and associative approach. Data was collected through questionnaires and analyzed using SmartPLS 3.0 through outer model tests, inner models, and hypothesis tests. The results of the study showed that 1) leadership style has a significant effect on employee performance, 2) leadership style has a significant effect on organizational culture, 3) organizational culture has a significant effect on employee performance, 4) there is an indirect influence of leadership style on employee performance through organizational culture, although the direct influence is greater. Thus, organizational culture plays a role in improving employee performance, but it does not strengthen the relationship between leadership style and employee performance.